2012
DOI: 10.1088/0953-8984/24/46/464101
|View full text |Cite
|
Sign up to set email alerts
|

Depletion induced clustering in mixtures of colloidal spheres andfd-virus

Abstract: We determined the phase boundary of an ideal rod-sphere mixture consisting of fd-virus, which is an established model system for mono-disperse colloidal rods, and density matched mono-disperse polystyrene beads employing diffuse wave spectroscopy. The low volume fraction of fd needed to induce a phase separation at relatively low ionic strength exemplifies the fact that slender rods are very effective depletion agents. Confocal microscopy showed that stable clusters are formed during phase separation. Relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Thus, the phase transition point lies between these two rod concentrations. All the experimental phase transitions measured here are liquid-liquid like, as determined with confocal laser scanning microscopy in a similar fashion as discussed in a previous paper 38 .…”
Section: B Experimental Methodologysupporting
confidence: 72%
See 3 more Smart Citations
“…Thus, the phase transition point lies between these two rod concentrations. All the experimental phase transitions measured here are liquid-liquid like, as determined with confocal laser scanning microscopy in a similar fashion as discussed in a previous paper 38 .…”
Section: B Experimental Methodologysupporting
confidence: 72%
“…The rod concentrations were much lower than in the experiments of Adams et al and the size ratio used was ξ = 3.5. Guu et al observed a transition from isotropic to an isostructural fluid/fluid coexistence upon increasing rod concentration, as predicted by FVT calculations 38 . However, there was a big discrepancy between the onset of phase separation predicted by FVT and the experimental results.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…These rod-shaped viruses, with a length of 880 nm and a width of 6 nm, form a cholesteric phase in bulk and are often used as a model system for liquid crystals [15][16][17][18][19][20][21][22].…”
Section: Application To Experimental Datamentioning
confidence: 99%